2014
DOI: 10.1159/000369275
|View full text |Cite
|
Sign up to set email alerts
|

Grading of Neuroendocrine Neoplasms: Mitoses and Ki-67 Are Both Essential

Abstract: Background: The current WHO classification for neuroendocrine neoplasms (NEN) of the gastrointestinal tract requires Ki-67 and mitotic index for grading. However, both indexes might be conflicting as far as grade is concerned. In this study, we investigate which of the two indexes is most informative to predict survival. Methods: We assessed 362 patients with NEN of gastrointestinal (n = 148), pancreatic (n = 29), lung (n = 77), unknown primary site (n = 102) and of miscellaneous (n = 6) origin. Follow-up and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 24 publications
0
38
0
Order By: Relevance
“…[23][24][25] In patients with discordant Ki-67 index and mitotic counts (up to 33% of cases), Ki-67, when elevated, is a better predictor for tumor biology. 26 Although tumor grade had no influence on a patient undergoing cytoreductive surgery in the SEER-Medicare cohort, patients with well-differentiated metastatic NET from GI primary were more likely to be treated with S-LAR than their counterparts. It has also been shown that patients with a robust T cell (CD3þ) tumor infiltrate have a superior outcome when compared with those with tumors containing high levels of infiltrating regulatory T cells.…”
Section: Discussionmentioning
confidence: 95%
“…[23][24][25] In patients with discordant Ki-67 index and mitotic counts (up to 33% of cases), Ki-67, when elevated, is a better predictor for tumor biology. 26 Although tumor grade had no influence on a patient undergoing cytoreductive surgery in the SEER-Medicare cohort, patients with well-differentiated metastatic NET from GI primary were more likely to be treated with S-LAR than their counterparts. It has also been shown that patients with a robust T cell (CD3þ) tumor infiltrate have a superior outcome when compared with those with tumors containing high levels of infiltrating regulatory T cells.…”
Section: Discussionmentioning
confidence: 95%
“…The Ki‐67 proliferation index, however, may be valuable for cases difficult to classify, including TC–AC and AC–HGNEC borderline cases . This is especially true for small biopsy specimens where it is difficult to screen 2 mm for mitotic cells, and some studies even indicate that Ki‐67 may outperform histopathological classification in biopsy material . This warrants an extensive study comparing performance of the WHO classification and Ki‐67 on a series of lung NETs for which both biopsy and resection material is available.…”
Section: Discussionmentioning
confidence: 99%
“…The 2014 review by Pelosi et al describes the many different immunohistochemical evaluation systems used for Ki-67 measurement [8, 9, 1214, 31, 32]. In the present study, we compared two widely used manual counting methods, the Ki-67-Average (magnification 400×, per 10 representative HPFs) and the Ki-67-Hotspot evaluation (magnification 400×, per 2000 cells), with each other and with a fully automated digital image analysis of Ki-67 IHC.…”
Section: Discussionmentioning
confidence: 99%